A STRATEGI GURU DALAM MENERAPKAN PEMBELAJARAN DIFERENSIASI PADA SISWA SLOW LEARNER DI SEKOLAH DASAR - Fajar Sri Utami; Hana Fatimah; Choiriyah Widyasari; Minsih Minsih (JPI (Jurnal Pendidikan Inklusi), 2026)
This study aims to describe teacher strategies in implementing differentiated learning for slow learners and identify supporting and inhibiting factors in its implementation in elementary schools. The research approach used was descriptive qualitative, with subjects consisting of a fifth-grade teacher and three slow learner students at SD Negeri 1 Canden. Data were collected through observation, interviews, and documentation, then analyzed descriptively. The research results show that teachers implement differentiated learning through three main components: content, process, and product differentiation. In content differentiation, teachers simplify language, use concrete media, and repeat explanations to help slow learners better understand the material. In process differentiation, teachers provide additional time, individual guidance, and peer support. Meanwhile, in product differentiation, teachers provide flexibility in learning outcomes according to students' abilities. Supporting factors include teacher commitment, peer support, and student motivation. Inhibiting factors include time constraints, minimal training, and inadequate facilities. Overall, teacher strategies demonstrate positive efforts toward inclusive and adaptive learning for slow learners, although professional training and adequate learning resources are still needed to increase their effectiveness